2019
DOI: 10.1016/j.ygeno.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Classification and experimental identification of plant long non-coding RNAs

Abstract: Our understanding of gene regulation is constantly evolving. It is now clear that the majority of cellular transcripts are non-coding RNAs. The spectrum of non-coding RNAs is diverse and includes short (<200 nt) and long non-coding RNAs (lncRNAs) (>200 nt). LncRNAs regulate gene expression through diverse mechanisms. In this review, we describe the emerging roles of lncRNA mediated plant gene regulation. We discuss the current classification of lncRNAs and their role in genome organization and gene regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 132 publications
3
66
0
Order By: Relevance
“…Unlike Pol II transcripts, these lncRNAs are less characterized and possess some structural differences such as lack of poly-A tails (Zhou and Law, 2015). Identification of RNA Pol IV or PolV transcribed lncRNAs is particularly challenging due to their extremely low expression and instability (Rai et al, 2018). However, these transcripts are the major players driving RNA-mediated DNA methylation (RdDM).…”
Section: Biogenesis Of Lncrnasmentioning
confidence: 99%
“…Unlike Pol II transcripts, these lncRNAs are less characterized and possess some structural differences such as lack of poly-A tails (Zhou and Law, 2015). Identification of RNA Pol IV or PolV transcribed lncRNAs is particularly challenging due to their extremely low expression and instability (Rai et al, 2018). However, these transcripts are the major players driving RNA-mediated DNA methylation (RdDM).…”
Section: Biogenesis Of Lncrnasmentioning
confidence: 99%
“…Nevertheless, there are some plant lncRNAs whose regulatory functions have been studied extensively and are understood at a level of detail comparable to most proteins (Rai et al, 2018): COOLAIR in Brassicaceae has a crucial role in the vernalization process (Hawkes et al, 2016) and its transcription accelerates epigenetic silencing of the flowering locus C (FLC) (Rosa et al, 2016). The lncRNA HID1, a key component in promoting photomorphogenesis in response to different levels of red light (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 14 loci did not have transcriptional evidence (Table S7, Supplementary File S2). Units 5S (34), 5.8S (8), two fragments from a large ribosomal subunit, five fragments from a small ribosomal subunit were identified, while two were indeterminate. Twenty-one high-confidence rRNA regions were identified in the pseudomolecule "Chromosome 0".…”
Section: Ribosomal Rnasmentioning
confidence: 99%
“…In plants, most studies usually identify a single class of ncRNAs, such as miRNAs or long non-coding RNAs [4][5][6][7][8]. Although several studies have identified miRNAs in plants [9][10][11], the identification has not always been performed in the most reliable way [12].…”
Section: Introductionmentioning
confidence: 99%